Identification of Genes Related to 5-Fluorouracil Based Chemotherapy for Colorectal Cancer - Huang, Xingxing; Ke, Kun; Jin, Weiwei; Zhu, Qianru; Zhu, Qicong; Mei, Ruyi; Zhang, Ruonan; Yu, Shuxian; Shou, Lan; Sun, Xueni; Feng, Jiao; Duan, Ting; et al. (Frontiers in Immunology, 2022)
Background: Colorectal cancer (CRC) is one of the most common malignancies, and its incidence and mortality are increasing yearly. 5-Fluorouracil (5-FU) has long been used as a standard first-line treatment for CRC patients. Although 5-FU-based chemotherapy is effective for advanced CRC, the consequent resistance remains a key problem and causes the poor prognosis of CRC patients. Thus, there is an urgent need to identify new biomarkers to predict the response to 5-FU-based chemotherapy. Methods: CRC samples were retrieved from Gene Expression Omnibus (GEO) and The Cancer Genome Atlas (TCGA). The immune-related genes were retrieved from the ImmPort database. Single-cell sequencing results of colorectal cancer were obtained by the ArrayExpress database. The genes related to 5-FU resistance were filtered and validated by R packages. ESTIMATE algorithms were used to assess the tumor microenvironment (TME). KEGG and GO analysis were performed to explore the biological signaling pathway for chemotherapy-resistant and chemotherapy-sensitive patients in the tumor microenvironment. Results: 9 immune-related genes were identified to be associated with 5-FU resistance and poor disease-free survival (DFS) of CRC patients. And the signature of these genes was developed in a DFS-prognostic model. 4 immune-related genes were determined to be associated with 5-FU resistance and overall survival (OS) of CRC patients. The signature of these genes was developed an OS-prognostic model. ESTIMATE scores showed a significant difference between 5-FU resistant and 5-FU sensitive CRC patients. Resistant-response and sensitive patients to 5-FU based chemotherapy showed different GO and KEGG enrichment on the tumor microenvironment. RBP7, as a tumor immune microenvironment (TIME) related gene, was found to have the potential of predicting chemotherapy resistance and poor prognosis of CRC patients. GSEA analysis showed multiple signaling differences between the high and low expression of RBP7 in CRC patients. Single-cell RNA-seq suggested RBP7 was centrally distributed in endothelial stalk cells, endothelial tip cells, and myeloid cells. Conclusions: Immune-related genes will hopefully be potential prognostic biomarkers to predict chemotherapy resistance for CRC. RBP7 may function as a tumor microenvironment regulator to induce 5-FU resistance, thereby affecting the prognosis of CRC patients.